IFSI-guideline on chronic prurigo including prurigo nodularis. Issue 4 (18th October 2020) - Ständer, Sonja; Pereira, Manuel P.; Berger, Timothy; Zeidler, Claudia; Augustin, Matthias; Bobko, Svetlana; Brenaut, Emilie; Chen, Suephy C.; Chisolm, Sarah; Dalgard, Florence J.; Elberling, Jesper; Elmariah, Sarina B.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Chronic prurigo (CPG) is a highly burdensome pruritic disease characterized by chronic itch, a prolonged scratching behavior and the development of localized or generalized hyperkeratotic pruriginous lesions. Neuronal sensitization and the development of an itch-scratch cycle contribute to the augmentation of pruritus and the chronicity of the disease. We provide here the first international guideline for a rational diagnostic and therapeutic approach for CPG. Recommendations are based on available evidence and expert opinion. The diagnosis of CPG is made clinically. A detailed medical history together with laboratory and radiological examinations are advised in order to determine the severity of CPG, identify the underlying origin of the itch and assist in the elaboration of a treatment plan. Therapeutically, it is advised to adopt a multimodal approach, including general strategies to control itch, treatment of the underlying pruritic conditions, and of the pruriginous lesions. Topical (corticosteroids, calcineurin inhibitors, capsaicin) and systemic antipruritic agents (eg, gabapentinoids, immunosuppressants, and opioid modulators) as well as physical treatment modalities (phototherapy, cryotherapy) should be employed in a step-wise approach. Psychosomatic or psychological interventions may be recommended in CPG patients with signs of psychiatric/psychological comorbidities.